Nilai Pedagosis dalam Ritual Domyak - Prawiyogi, Anggy Giri; Dwimarwati, Retno; Afryanto, Suhendi (PANTUN: Jurnal Ilmiah Seni Budaya, 2022)
Domyak is a ritual means of asking for rain at the foot of Mount Burangrang, Pasir Angin Village, Darang District and Purwakarta Regency. In 1920, domyak was called chickpeas but in 1990 it became domyak (ngadogdog and rampayak) meaning playing dogdog music with dances. This paper aims to examine the pedagogical values contained in the domyak ritual and the domyak ritual process. The presentation is carried out in several stages which are also accompanied by several forms of performing arts. The domyak ritual is performed in the form of helaran or procession or using a stage. Bloom’s taxonomic theory is applied to explore pedagogical values in domyak rituals. Qualitative data were collected through observation, interviews, and documentation. The results of the study include the pedagogical values contained in the goals of education, educational content, and educational tools used. The purpose of education is that each of the member of the communities should master traditional customs, especially in the domyak ritual to ask for rain; The contents of education are ritual traditions which have been passed down from generation to generation from the 1920s to the present; Educational tools used in the form of habituation, supervision, orders, prohibitions and rewards in these ritual activities, such as: in starting the ritual by praying and the command to bathe the cat in the ritual activity. Keywords: Pedagogical value, domyak ritual ABSTRAK Domyak merupakan sarana ritual meminta hujan yang berasal dari kaki Gunung Burangrang Desa Pasir Angin Kecamatan Darangdan Kabupaten Purwakarta. Pada tahun 1920 Domyak tersebut dinamakan buncis dan pada tahun 1990 berubah menjadi Domyak yang berarti (ngadogdog dan rampayak) bermain musik dogdog dengan tarian. Tulisan ini bertujuan untuk mengkaji nilai-nilai pedagogis yang terdapat pada ritual Domyak serta poses ritual domyak. Penyajiannya dilakukan dalam beberapa tahapan-tahapan yang juga diiringi oleh beberapa bentuk seni pertunjukan. Ritual Domyak dipertunjukkan dalam bentuk helaran atau arak-arakan maupun menggunakan panggung. Teori taksonomi Bloom digunakan untuk menggali nilai-nilai pedagogis dalam ritual domyak. Data kualitatif dikumpulkan melalu observasi, wawancara, dan dokumentasi. Hasil Penelitian mencakup nilai-nilai pedagogis yang terdapat dalam tujuan pendidikan, pendidikan, isi pendidikan serta alat pendidikan yang digunakan. Tujuan pendidikan yakni setiap warga masyarakat harus menguasai adat tradisi terutama dalam ritual Domyak untuk meminta hujan; Isi pendidikan yakni tradisi ritual yang diturunkan secara turun temurun dari tahun 1920 sampai saat ini; Alat pendidikan yang digunakan berupa pembiasaan, pengawasan, perintah, larangan dan ganjaran dalam kegiatan ritual tersebut, seperti: dalam memulai ritual dengan berdoa dan perintah untuk memandikan kucing dalam kegiatan ritual tersebut. Kata Kunci: Nilai pedagogis, ritual domyak